A multi-cohort study of the immune factors associated with M. tuberculosis infection outcomes. (30th August 2018) - Roy Chowdhury, Roshni; Vallania, Francesco; Yang, Qianting; Lopez Angel, Cesar; Darboe, Fatoumatta; Penn-Nicholson, Adam; Rozot, Virginie; Nemes, Elisa; Malherbe, Stephanus; Ronacher, Katharina; Walzl, Gerhard; Hanekom, Willem; et al.
Abstract Most infections withMycobacterium tuberculosis (Mtb ) manifest as a clinically asymptomatic, contained state, known as latent tuberculosis infection, that affects approximately one-quarter of the global population1 . Although fewer than one in ten individuals eventually progress to active disease2, tuberculosis is a leading cause of death from infectious disease worldwide3 . Despite intense efforts, immune factors that influence the infection outcomes remain poorly defined. Here we used integrated analyses of multiple cohorts to identify stage-specific host responses toMtb infection. First, using high-dimensional mass cytometry analyses and functional assays of a cohort of South African adolescents, we show that latent tuberculosis is associated with enhanced cytotoxic responses, which are mostly mediated by CD16 (also known as FcγRIIIa) and natural killer cells, and continuous inflammation coupled with immune deviations in both T and B cell compartments. Next, using cell-type deconvolution of transcriptomic data from several cohorts of different ages, genetic backgrounds, geographical locations and infection stages, we show that although deviations in peripheral B and T cell compartments generally start at latency, they are heterogeneous across cohorts. However, an increase in the abundance of circulating natural killer cells in tuberculosis latency, with a corresponding decrease during active disease and a return to baseline levels upon clinical cure are features that are common to all cohorts. Furthermore, by analysing three longitudinal cohorts, we find that changes in peripheral levels of natural killer cells can inform disease progression and treatment responses, and inversely correlate with the inflammatory state of the lungs of patients with active tuberculosis. Together, our findings offer crucial insights into the underlying pathophysiology of tuberculosis latency, and identify factors that may influence infection outcomes. Integrated analyses of multiple cohorts are used to obtain a better understanding of the immune state of latent infection withMycobacterium tuberculosis, and factors that mediate and/or predict transitions from latent infection to active disease.